Cardiorespiratory fitness in 16 025 adults aged 18–91 years and associations with physical activity and sitting time. Issue 12 (17th December 2015) - Eriksen, L.; Grønbæk, M.; Helge, J. W.; Tolstrup, J. S.
Abstract : Our aim was to provide up‐to‐date cardiorespiratory fitness reference data for adults of all ages and to investigate associations between cardiores‐piratory fitness and leisure time physical activity as well as sitting time. In the Danish Health Examination Survey 2007–2008, cardiorespiratory fitness was estimated in 16 025 individuals aged 18–91 years from validated cycle ergometer exercise tests. Level of leisure time physical activity (sedentary, light, moderate, and vigorous) and daily sitting time in hours was obtained from a self‐administered questionnaire. Men had 20–33% higher cardiorespiratory fitness than women, depending on age, and cardiorespiratory fitness decreased by 0.26 and 0.23 mL/min/kg per year in men and women, respectively. Cardiorespiratory fitness was higher among participants who reported a high level of physical activity in leisure time compared with participants who were sedentary. Among sedentary or lightly physically active participants, inverse associations between total daily sitting time and cardiorespiratory fitness were found, while there was no association between sitting time and cardiorespiratory fitness among moderately or vigorously physically active participants. These data on cardiorespiratory fitness can serve as useful reference material. Although reluctant to conclude on causality, sitting time might impact cardiorespiratory fitness among individuals with low levels of leisure time physical activity.